Pengembangan Desain Pembelajaran dengan Pendekatan Gamifikasi sebagai Strategi Menumbuhkan Motivasi Belajar Siswa - Prasetyo, Rizky Budi; Aziz, Tian Abdul (Lembaga Yasin AlSys, 2025)
The low level of student motivation in learning matrix material in Grade XI of senior high school caused by the abstract nature of the topic and the use of conventional teaching methods forms the background of this study. The objective is to develop a gamification-based instructional design to enhance students’ learning motivation. This research adopts the Research and Development (R&D) method using the Four-D model (Define, Design, Develop, Disseminate), limited to the Develop stage. The research subjects consisted of 24 Grade XI students. Data were collected through a learning motivation questionnaire based on the ARCS model (Attention, Relevance, Confidence, Satisfaction) and validated using the V-Aiken index. The findings indicate that the gamification-based instructional design is valid and feasible for use. A limited trial showed that this approach is effective in fostering learning motivation, with 75% of students expressing a positive response toward the model. The study provides important implications for teachers in integrating gamification elements as an interactive teaching strategy to enhance student engagement in mathematics learning.